Immunotherapy of CT26 murine tumors is characterized by an oligoclonal response of tissue‐resident memory T cells against the AH1 rejection antigen. Issue 10 (9th June 2020) - Stringhini, Marco; Probst, Philipp; Neri, Dario
Abstract: Mice bearing CT26 tumors can be cured by administration of L19‐mIL12 or F8‐mTNF, two antibody fusion proteins which selectively deliver their cytokine payload to the tumor. In both settings, cancer cures crucially depended on CD8 + T cells and the AH1 peptide (derived from the gp70 protein of the murine leukemia virus) acted as the main tumor‐rejection antigen, with ∼50% of CD8 + T cells in the neoplastic mass being AH1‐specific after therapy. In order to characterize the clonality of the T cell response, its phenotype, and activation status, we isolated CD8 + T cells from tumors and secondary lymphoid organs and submitted them to T cell receptor (TCR) and total mRNA sequencing. We found an extremely diverse repertoire of more than 40 000 unique TCR sequences, but the ten most abundant TCRs accounted for >60% of CD8 + T‐cell clones in the tumor. AH1‐specific TCRs were consistently found among the most abundant sequences. AH1‐specific T cells in the tumor had a tissue‐resident memory phenotype. Treatment with L19‐mIL12 led to overexpression of IL‐12 receptor and of markers of cell activation and proliferation. These data suggest that the antitumor response driven by antibody‐cytokine fusions proceeds through an oligoclonal expansion and activation of tumor‐infiltrating CD8 + T cells. Abstract : The study employs T cell receptor sequencing and transcriptome analysis to show that CD8 + T cells infiltrating CT26 tumors are oligoclonal, mostly specific for the retroviral peptide AH1 and have a tissue‐resident memory phenotype. Upon immunotherapy treatment, AH1 specific T cells show signs of increased activation and proliferation.